Measurement of tibial slope angle after medial opening wedge high tibial osteotomy: case series - Yanasse, Ricardo Hideki; Cavallari, Carlos Eduardo; Chaud, Felipe Lourenço; Hernandez, Arnaldo José; Mizobuchi, Roberto Ryuiti; Laraya, Marcos Henrique (São Paulo Medical Journal, 2009)
CONTEXT AND OBJECTIVE: In the past, changes in tibial slope were not considered when planning or evaluating osteotomies, and success in high tibial osteotomy was related to the alignment and amount of femorotibial angular correction. The aim here was to measure changes in tibial slope after medial opening wedge tibial osteotomy and investigate the effect of tibial slope angle on the clinical results. DESIGN AND SETTING: Retrospective review study on a series of cases, at the Department of Orthopedics and Traumatology, Faculdade de Medicina de Marília (Famema), Marília, Brazil. METHODS: Twenty-eight patients were studied, and a total of thirty-one knees. Lateral roentgenograms of the tibia were used pre and postoperatively to measure the tibial slope based on the proximal tibial anatomical axis. The clinical results were measured using the Lysholm knee score. RESULTS: There was an average increase in tibial slope angle after surgery of 2.38° (95% confidence interval: ± 0.73°). There was no correlation (r = -0.28) between the postoperative Lysholm knee score and the difference in tibial slope angle from before to after surgery (P = 0.13). CONCLUSION: Medial opening wedge tibial osteotomy led to a small increase in tibial slope. No significant correlation was found between increased tibial slope and short-term clinical results after high tibial osteotomy. Other clinical studies are needed in order to establish whether extension or flexion osteotomy could benefit patients with medial compartment gonarthrosis.